2016
DOI: 10.1007/s00167-016-4125-y
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative approaches for the treatment of early OA

Abstract: The diagnosis and the prompt treatment of early osteoarthritis (OA) represent vital steps for delaying the onset and progression of fully blown OA, which is the most common form of arthritis, involving more than 10 % of the world's population older than 60 years of age. Nonsurgical treatments such as physiotherapy, anti-inflammatory medications, and other disease-modifying drugs all have modest and short-lasting effect. In this context, the biological approaches have recently gained more and more attention. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 65 publications
0
48
0
3
Order By: Relevance
“…The therapeutic potential of MSCs have been largely investigated in in vitro and preclinical settings, as well as in many studies at clinical level, for their ability to improve healing from orthopedic conditions such as chondral lesion [16], osteoarthritis [17], tendinopathy [18], intervertebral disk disease [19], and bone non-union/delayed unions [20]. MSCs have been used either expanded [21] or as concentrated progenitor pools [22], both with satisfactory results.…”
Section: Mesenchymal Stem Cells: a Multimodal Tool To Treat Musculoskmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic potential of MSCs have been largely investigated in in vitro and preclinical settings, as well as in many studies at clinical level, for their ability to improve healing from orthopedic conditions such as chondral lesion [16], osteoarthritis [17], tendinopathy [18], intervertebral disk disease [19], and bone non-union/delayed unions [20]. MSCs have been used either expanded [21] or as concentrated progenitor pools [22], both with satisfactory results.…”
Section: Mesenchymal Stem Cells: a Multimodal Tool To Treat Musculoskmentioning
confidence: 99%
“…Even if further studies are needed to confirm their utility and to standardize applications, the results of the use of MSCs in orthopedic conditions are very promising and many studies are nowadays ongoing [17]. …”
Section: Mesenchymal Stem Cells: a Multimodal Tool To Treat Musculoskmentioning
confidence: 99%
“…Despite extensive preclinical research with promising results, because of its technical limitations such as deinition on the optimal cell source, processing, assembly with scafolding, and administration modality, the use in patients is not yet overwhelming, and the design of a systematic procedure is still to be addressed [34,35,153,154].…”
Section: Cartilage Injuries and Osteoarthritismentioning
confidence: 99%
“…For patients with early or middle stage OA, a non-arthroplasty treatment regime is typically prescribed, which is focused on the control of symptoms including the imbalance of cartilage homeostasis (13). Previous studies have demonstrated that chitosan and its derivatives may serve a protective role in OA (14,15).…”
Section: Introductionmentioning
confidence: 99%